KEMAMPUAN PENALARAN MATEMATIS SISWA DALAM MENYELESAIKAN SOAL PADA MATERI RELASI DAN FUNGSI KELAS VIII SMP - Veronica Veronica Siskanti (Universitas Sriwijaya, 2021)
The aims of this study is to describe students' mathematical reasoning skills in solving problems on relationship materials and functions. Research method is used descriptive qualitative. The research subjects consisted of six students of grade VIII SMP Negeri 51 Palembang with two students with high ability, two medium students and two students with low ability. Data collection is carried out by providing 5 points about tests, interviews, and documentation. This study, using 5 indicators of reasoning, namely analysis, synthesis, generalization, problem solving is not routine, and justification / proof. The results showed that students who have high ability are mostly able to fulfill all aspects of mathematical reasoning ability. As for students who have moderate ability is able to meet two to three aspects of the students' mathematical reasoning ability only. Then for students who have low ability is only able to meet one to two aspects of the student's mathematical reasoning ability.